Tinder Use and Romantic Relationship Formations: A Large-Scale Longitudinal Study - Erevik, Eilin K.; Kristensen, Joakim H.; Torsheim, Torbjørn; Vedaa, Øystein; Pallesen, Ståle (Frontiers in Psychology, 2020)
The current paper aims to investigate if Tinder use predicts romantic relationship formation one year later, and to identify demographic, personality, mental health and substance use covariates in the relationship between Tinder use and romantic relationship formation. Data were collected by online surveys (two waves) among students in Bergen, Norway. The first survey was administered during fall 2015. The follow-up took place one year later (fall 2016). The sample consisted of 5,253 participants who reported being single at the time of the first survey. The surveys included questions about Tinder use, demographics, personality (the five-factor model’s personality traits), mental health (i.e., symptoms of depression and anxiety), alcohol use and use of illegal substances. Bivariate comparisons were conducted to assess differences in demographics, personality traits, mental health and substance use between Tinder users and non-Tinder users. Further, crude and adjusted binary logistic regressions were employed to investigate if Tinder use at the time of the fist survey predicted romantic relationship formation at the time of the follow-up, when controlling for relevant covariates. Tinder users differed from non-users on almost all the included variables. Compared to non-users, Tinder users were younger and more likely to be men, born in Norway, childless and non-religious. Tinder users had higher scores on extroversion and agreeableness and lower scores on openness than non-users. Further, compared to non-users, Tinder users reported more symptoms of anxiety, were more likely to have hazardous, harmful or dependent alcohol use and to report use of illegal substances. Compared to non-users, Tinder users had a higher likelihood of having formed a romantic relationship at the time of the follow-up in the crude model (p < .05), and when controlling for demographic (p < .05) and mental health (p < .05) covariates. However, when controlling for personality, substance use, and all included covariates, the difference in likelihood of having formed a romantic relationship was no longer significant. In conclusion, the current results suggest that Tinder users have a higher likelihood of forming romantic relationship longitudinally, but that this mainly can be explained by Tinder users’ personality and substance use characteristics.